Prevalence of hepatitis D virus among HBsAg-positive individuals,2015-2016: Azar cohort study - Ali Asghar Pouri; Morteza Ghojazadeh; Babak Baiaz; Fatemeh Soghra Hamzavi; Behrouz Pourasghari; Mohammad Hossein Somi (Tabriz University of Medical Sciences, 2020)
Background: Hepatitis D virus (HDV) is a defective RNA pathogen that requires the presence of the hepatitis B virus (HBV) for infection. Middle East countries are endemic areas for HDV infection. So, it is important to estimate the prevalence of HDV in these countries. This study aimed to estimate the prevalence of HDV in HBsAg positive patients participated in Azar cohort study, North-west of Iran. Methods: In this cross-sectional study, out of 4949 participants of the Azar cohort study, 51HBsAg positive patients were selected. Five participants did not consent to HDV testing. The presence of anti-HDV IgG was checked in 46 patients (13 chronic hepatitis B and 33 inactive chronic hepatitis B) using enzyme-linked immunosorbent assay (ELISA) kit. The serum level of liver enzymes was measured and a questionnaire about risk factors was completed. Results: In this study, the mean age of HBsAg positive patients was 50.06 (SD 9.14) years and41.3% were female. Only one out of 46 patients was positive for HDV infection. Thus, the prevalence of HDV infection among hepatitis B virus surface antigen (HBsAg) positive patients was 2.17% (95% CI: 0.1-11.5). The positive anti-HDV patient was in the inactive chronic hepatitis B state and she had a history of hospitalization and dental procedures. Conclusion: The results showed that the prevalence of HDV infection in HBsAg positive patients was 2.1% that was lower than the reported prevalence in many other regions of Iran. Health policymakers and healthcare providers should design coherent and orderly epidemiological studies for planning and monitoring HDV infection.